"We're Brokers": How Youth Violence Prevention Workers Intervene in the Lives of At-Risk Youth to Reduce Violence. (September 2020) - Free, Janese L.
This study explores the strategies youth violence prevention workers (YVPWs) employ to intervene in the lives of at-risk youth. Data drawn from 47 in-depth interviews with YVPWs in a large city in the northeastern United States revealed five main strategies they use to reduce violence, namely (1) sharing information with other YVPWs, (2) collaborating and networking with the community, (3) "being a presence" and building relationships with clients, (4) responding to clients' conflicts and crises, and (5) providing clients and their families with resources and advocacy. Focused deterrence theory and pulling levers strategy are used to explain the findings and policy and program recommendations are discussed.